2021
DOI: 10.1186/s13227-021-00177-y
|View full text |Cite
|
Sign up to set email alerts
|

Panarthropod tiptop/teashirt and spalt orthologs and their potential role as “trunk”-selector genes

Abstract: Background In the vinegar fly Drosophila melanogaster, the homeodomain containing transcription factor Teashirt (Tsh) appears to specify trunk identity in concert with the function of the Hox genes. While in Drosophila there is a second gene closely related to tsh, called tiptop (tio), in other arthropods species only one copy exists (called tio/tsh). The expression of tsh and tio/tsh, respectively, is surprisingly similar among arthropods suggesting that its function as trunk selector gene may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In Drosophila , the single Dbx gene is expressed in interneurons that form from a subset of neural progenitor cells (neuroblasts) [ 106 ]. Finally, the trunk-determining zinc finger transcription factor tiptop/teashirt ( tio/tsh ) (LOC107441771) is expressed in the CNS of the trunk of Parasteatoda [ 125 , 129 ]. In Drosophila , tio and tsh are expressed in the trunk CNS as well, and it has been shown that both genes can mediate the survival of neurons [ 107 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila , the single Dbx gene is expressed in interneurons that form from a subset of neural progenitor cells (neuroblasts) [ 106 ]. Finally, the trunk-determining zinc finger transcription factor tiptop/teashirt ( tio/tsh ) (LOC107441771) is expressed in the CNS of the trunk of Parasteatoda [ 125 , 129 ]. In Drosophila , tio and tsh are expressed in the trunk CNS as well, and it has been shown that both genes can mediate the survival of neurons [ 107 , 135 ].…”
Section: Resultsmentioning
confidence: 99%